Transformation of the detective genre in a French novel at the turn of the 20th and 21st centuries - Efimenko, Hanna O. (Journal of the Belarusian State University. Philology, 2023)
The process of transformation of the detective genre within the framework of the French literary tradition at the turn of the 20th and 21st centuries is described. The subgenres that determined the development vector of French detective prose are identified. The genre diversity of French literature is substantiated through the connection between the avant-garde and postmodernism. The specifics of the author’s manner, as well as the peculiarities of the influence of the schools and trends to which the writers belong, on the way the genre of the detective story is transformed in their works are analysed. The philosophical and aesthetic approach to the exploitation of the structural model of the detective is considered. The transformation of the detective novel is shown taking into account the tendencies of the neoavant-garde and postmodernism, which allows us to study the national identity of the genre in more detail.